Enhancing Community Knowledge on Homemade Biolarvicide from Citrus aurantifolia Against Dengue Vector in Sukoanyar Village Lamongan - Nur Lathifah Syakbanah; Eko Sulistiono; Marsha Savira Agatha Putri; Gading Wilda Aniriani; Rizky Rahadian Wicaksono; Muhammad Hanif; Danang Eka Riantara Romadhon; Tri Madiyaningsih (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Community education and routine use of insecticides are implemented by the government to reduce dengue vectors. Chemical insecticides and larvicides kill mosquitoes faster and optimally, but massive use in the long term will cause resistance effects. Limonoids and flavonoids in Citrus aurantifolia could be substitute temephos in abate. The study aims to enhance community knowledge on homemade biolarvicide from lime leaves and peels (Citrus aurantifolia) powder against dengue vector in Sukoanyar Village, Lamongan. Target of community education is women who are members of PKK in the Sukoanyar Village, Lamongan. The activities consist of educational sessions about dengue vector control, vector resistance, lime (Citrus aurantifolia) as biolarvicide, and distribution of trifold brochure media. Then, cognitive test sessions were conducted in pre-tests and post-tests. Results showed that the community was very enthusiastic about making powdered lime leaves and peels (Citrus aurantifolia) as homemade biolarvicide. Moreover, women in Sukoanyar Village have good knowledge (85,5%) about dengue vector control and biolarvicides then increasing to 90,9% during post-test. It was concluded that community knowledge improved regarding dengue vector control and the use of homemade biolarvicide from powdered lime leaves and peels (Citrus aurantifolia) in tea bags as substitute for abate.